2017
DOI: 10.21608/smj.2017.40737
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesic efficacy of bupivacaine with hyalourindase in TAP block for lower abdominal surgeries

Abstract: Aim :To evaluate the effect of addding hyalourindase to bupivacaine in TAP block for lower abdominal surgeries as postoperative analgesia. Methods : fifty patients aged between 20-60 years who were scheduled for lower abdominal surgeries included in the study and divided into two groups,after approval of ethical committee.This study conducted in Sohag university hospitals from September 2016 to March 2017. Patients were divided into two equal groups and all received spinal anesthesia :-(Group A) 25 patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Our study was supported by Salah et al [22] in 2017 who concluded that addition of hyalourindase to bupivacaine for transversus abdominis plane (TAP) block resulted in significant reduction in VAS pain score over the post-operative 24hours and reduction of postoperative morphine requirements.…”
Section: Discussionsupporting
confidence: 77%
“…Our study was supported by Salah et al [22] in 2017 who concluded that addition of hyalourindase to bupivacaine for transversus abdominis plane (TAP) block resulted in significant reduction in VAS pain score over the post-operative 24hours and reduction of postoperative morphine requirements.…”
Section: Discussionsupporting
confidence: 77%